Climate drivers and animal host use determine kelp performance over decadal scales in the kelp Pleurophycus gardneri (Laminariales, Phaeophyceae). Issue 1 (15th November 2017) - Pfister, Catherine A.; Betcher, Samuel P.
Abstract : Primary producers respond to climate directly and indirectly due to effects on their consumers. In the temperate coastal ocean, the highly productive brown algae known as kelp have both strong climate and grazer linkages. We analyzed the demographic response of the kelp Pleurophycus gardneri over a 25‐year span to determine the interaction between ocean climate indicators and invertebrate infestation rates. Pleurophycus hosts amphipod species that burrow in the stipe, increasing mortality. Although kelp performance is generally greater with more negative values of the Pacific Decadal Oscillation (PDO) and colder seawater temperatures, Pleurophycus showed the opposite pattern. When we compared the 1990s, a period of positive values for the PDO and warmer sea surface temperatures, with the following decade, a period characterized by negative PDO values, we documented a contradictory outcome for proxies of kelp fitness. In the 1990s, Pleurophycus unexpectedly showed greater longevity, faster growth, greater reproductive effort, and a trend toward decreased amphipod infestation compared with the 2006–2012 period. In contrast, the period from 2006 to 2012 showed opposite kelp performance patterns and with a trend toward greater amphipod infestation. Pleurophycus performance metrics suggest that some coastal primary producers will respond differently to climate drivers, particularly if they interact strongly with grazers.